2006
DOI: 10.1055/s-2006-921564
|View full text |Cite
|
Sign up to set email alerts
|

Sensomotorisches Training im Alter und bei Osteoporose

Abstract: Vor dem Hintergrund der hohen Sturzhäufigkeit bei älteren Menschen, insbesondere bei Osteoporosepatienten, war es zentrales Anliegen dieser Studie, ein sensomotorisches Trainingsprogramm auf dem Aero Step zu entwickeln und in einer kontrollierten Längsschnittuntersuchung im Baselinedesign zu evaluieren. In die Studie wurden gesunde Ältere (n = 20; Durchschnittsalter 64,1 Jahre) und Osteoporosepatienten (n = 27; Durchschnittsalter 68,5 Jahre) eingeschlossen und bezüglich der Parameter Sensomotorik (Haltungs-und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Improvement of sensomotor abilities appears to exert a positive impact on quality of life. Schwesig et al [14] performed sensomotor exercises with the Aero-Step in 20 healthy elderly persons and 27 patients with osteoporosis aged on average 66.6 years. After conclusion of the training program the authors observed improvements in sensomotor performance and general wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of sensomotor abilities appears to exert a positive impact on quality of life. Schwesig et al [14] performed sensomotor exercises with the Aero-Step in 20 healthy elderly persons and 27 patients with osteoporosis aged on average 66.6 years. After conclusion of the training program the authors observed improvements in sensomotor performance and general wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…As recent advancements in sports medicine have proven the beneficial effects of sensomotor exercise on the regulation of posture and/or the frequency of falls [14,15], we decided to use sling exercise therapy. The procedure was developed by Kirkesola [16] to treat motor problems, and was established by Meier [17] for prevention as well as rehabilitation of professional German sportsmen.…”
Section: Introductionmentioning
confidence: 99%
“…Many elderly individuals suffer from comorbidities (such as deterioration of visual acuity or perception of contrast) which, however, culminate in physical imbalance only when combined with proprioception deficits. As recent advancements in sports medicine have proven the beneficial effects of sensomotor exercise on the regulation of posture and/or the frequency of falls [25,31], we decided to use sling exercise therapy. The procedure was developed by Kirkesola [12] to treat motor problems and was established by Meier [14] for prevention as well as rehabilitation of professional German sportsmen.…”
Section: Introductionmentioning
confidence: 99%
“…As recent advancements in sports medicine have proven the beneficial effects of sensomotor exercise on the regulation of posture and/or the frequency of falls (14,15), we decided to use sling exercise therapy. The procedure was developed by Kirkesola (16) to treat motor problems, and was established by Meier (17) for the prevention of conditions as well as rehabilitation in professional German sportsmen.…”
Section: Introductionmentioning
confidence: 99%